Implementasi Pembelajaran Berbasis Demonstrasi Pada Mata Pelajaran Fikih Materi Praktik Wudhu di SMA Al-Hasbi Cianjur - Delia Nur Aulia; Erni Susilawati; Tijanul Arifin; Cecep Hilman; Diansyah Permana (Jurnal Pendidikan Agama Islam, 2026)
Fiqh learning is one of the important efforts in instilling understanding and practice of Islamic teachings in students. However, in practice, some students still face difficulties in correctly understanding the procedures of wudu according to Islamic law. This study aims to determine the implementation of demonstration-based learning in Fiqh subjects on wudu practice material at Al-Hasbi Senior High School, Cilaku Cianjur. This research employs a qualitative approach with data collection techniques through interviews, observation, and documentation studies. The results show that the application of the demonstration method makes students more active, enthusiastic, and able to understand the steps of wudu correctly. In addition, teachers can more easily assess students’ practical abilities directly and correct mistakes in performing wudu. In conclusion, demonstration-based learning is effective in improving students’ understanding and skills in wudu practice in the Fiqh subject at Al-Hasbi Senior High School, Cilaku Cianjur.